Construction of magnetically recoverable ZnS–WO3–CoFe2O4 nanohybrid enriched photocatalyst for the degradation of MB dye under visible light irradiation. (June 2021) - Palanisamy, G.; Bhuvaneswari, K.; Bharathi, G.; Pazhanivel, T.; Grace, Andrews Nirmala; Pasha, S.K. Khadheer
Abstract: Easily recyclable photocatalysts have received considerable attention for their practical application, in order to address the wastewater treatments. Here, we report efficient and magnetically recyclable ZnS–WO3 –CoFe2 O4 nanohybrid prepared through wet impregnation method. The photophysical and optical properties of as-prepared photocatalysts was investigated by different spectroscopic techniques. The photocatalytic activity of as synthesized samples were assessed by the photodegradation of methylene blue (MB) dye under visible light irradiation. Amongst, ZnS–WO3 –CoFe2 O4 nanohybrid exhibit higher photodegradation activity than the other bare and hybrid samples. The enhanced light absorption and lower emission intensity provide the improved photocatalytic activity of ZnS–WO3 –CoFe2 O4 nanohybrid. The ZnS–WO3 –CoFe2 O4 nanohybrid exhibit excellent photostability after four consecutive cycles. The ferromagnetic behavior of the hybrid sample using easily recover from the dye solution using an external bar magnet. Graphical abstract: Image 1 Highlights: ZnS–WO3 –CoFe2 O4 nanohybrid prepared through wet impregnation method. The photocatalytic activity of ZnS–WO3 –CoFe2 O4 nanohybrid was investigated against MB dye. This nanohybrid exhibit higher photodegradation activity than the other samples. The ferromagnetic behavior of the hybrid sample using easily recover from the dye solution.